Ontogenesis of prolactin receptors in the human fetus in early gestation. Implications for tissue differentiation and development. - Freemark, M (1997)
To explore potential roles for lactogenic hormones in human fetal development, we examined the distribution and ontogenesis of expression of prolactin receptors (PRLRs) in human fetal tissues at 7.5-14 wk of gestation and in tissues of the embryonic and fetal rat on days e12.5-e20.5. Histochemical analysis of PRLR immunoreactivity in the human fetus and fetal rat revealed novel and unexpected patterns of receptor expression. Most remarkable was the appearance in early fetal development of intense PRLR immunoreactivity in tissues derived from embryonic mesoderm, including the periadrenal and perinephric mesenchyme, the pulmonary and duodenal mesenchyme, the cardiac and skeletal myocytes, and the mesenchymal precartilage and maturing chondrocytes of the endochondral craniofacial and long bones, vertebrae and ribs. Striking changes in the cellular distribution and magnitude of expression of PRLRs were noted in many tissues during development. In the fetal adrenal the initial mesenchymal PRLR expression is succeeded by the emergence of PRLR immunoreactivity in deeper fetal cortical cell layers. In the fetal kidney and lung, the invagination of cortical mesenchyme is accompanied by progressive PRLR immunoreactivity in bronchial and renal tubular epithelial cells. In the pancreas, the PRLR is expressed primarily in acinar cells and ducts in early gestation; in late gestation and in the postnatal period, the PRLR is expressed predominantly in pancreatic islets, co-localizing with insulin and glucagon. Finally in fetal hepatocytes, PRLR immunoreactivity increases significantly between embryonic days e52 and e96 in the human fetus and between days e16.5 and e18.5 in the fetal rat. In addition to playing important roles in reproduction, lactation, and immune function, the lactogenic hormones likely play roles in tissue differentiation and organ development early in gestation.